Gaya Bahasa Penegasan dalam Novel Buku Besar Peminum Kopi Karya Andrea Hirata - Salsadila Tudzahra; Samsiarni Samsiarni; Emil Septia (AIJER: Algazali International Journal Of Educational Research, 2023)
Abstract: The Style of Affirmation Language in Andrea Hirata's Big Book of Coffee Drinkers. This study aimsto find out the style of affirmative language in the novel The Big Book of Coffee Drinkers by Andrea Hirata. The type of research used in this study uses qualitative research methods, emphasizes more on the ways of interpretation presented in the form of descriptions, qualitative research focuses more on scientific data, qualitative research methods to describe and explain the meaning in literary works, the novel Buku Besar Peminum Kopi by Andrea Hirata . The results of this study show that in this literary work the author uses the stylistic style of affirmation, namely, pleonasm, repetition and rhetoric, and climax.